Influence of composite particle formation on the performance and economics of grit removal - Judd, Simon J.; Khraisheh, M.; Al-Jami, K. L.; Jarman, D. M.; Jahfer, T. (Elsevier, 2016)
Grit is routinely removed at the headworks of municipal wastewater treatment works to limit its onerous impact on downstream processes. Grit separation technologies are normally based on sedimentation of a homogeneous material (usually sand). However, in practice inorganic grit particles are likely to be combined with organic matter, such as fats oils and grease (FOG), producing a composite particle whose settling properties vary with the inorganic/organic content. A study of the impact of particle composition on its sedimentation has been conducted encompassing theoretical description (for particle settling in transitional flow), practical measurement and economic analysis. Practical measurement included sedimentation tests of homogeneous and composite particles along with characterisation of accumulated granular material sampled from actual municipal wastewater treatment works. The economic assessment was based on data from full-scale installations in the UK and US pertaining to remedial measures undertaken as a result of grit impacts, primarily accumulation in vessels and channels and damage of mechanical equipment through abrasion. Practical tests revealed coating of the sand grains with a FOG analogue (candlewax) to generate composite particles containing 45% wax by weight. The coated particles were then 30% less dense, 22% larger and 14% less settleable, on average, than the uncoated particles. Samples of accumulated grit taken from anaerobic digesters and aeration lanes from a full-scale plant indicated a FOG content (43%) similar to that of the waxed particles in the bench-scale tests, thus leading to a similar grain retardation of 14% assuming the FOG to be entirely associated with the grit. An assessment of the impact of the consequential breakthrough of grit particles due to buoyancy generated by composite particle formation indicated a $1.1 increase in operating costs per megalitre (ML) wastewater.
Keywords: Grit removal; Organic matter; Composite particle; Settling velocity; Transitional flow; Cost